SOCIAL ROLE OF VEGETABLE MERCHANTS IN OESAO MARKET TO MAINTAIN THE EXISTENCE OF THEIR CHILDREN AT SCHOOL - Srimulyati Ramadhan; Burhan Kiko (Sociology Education, Teaching Training and Education Faculty, Muhammadiyah University of Kupang, 2022)
The purpose of this study was to find out how the social role of vegetable merchants in Oesao Market, East Kupang District in maintaining the existence of their children at school. The research method used was qualitative. The informants consisted of vegetable merchants and children who study at school in Oesao District. The data were collected through in-depth interviews and documentation. This study showed several findings. First, the parents maintained their children at school by selling vegetables to meet their children's educational needs. Second, there were still many obstacles faced by parents in sending their children to school, especially the low economy. Third, the education fee was expensive, which was difficult for parents to send their children to school.